EFEKTIVITAS MEDIA GADGET MENURUT TEORI USES AND GRATIFICATION DALAM PEMBELAJARAN EKONOMI GUNA MEMBANGUN KETERAMPILAN SOSIAL SISWA KELAS XI DI SMA NEGERI 1 SIGI - Kapile, Natalia Veronica; Hasan, Hasan; Nuraedah, Nuraedah (Katalogis, 2020)
The main problem in this study is that most students own and use gadgets as a learning medium of economic. It is information from the students who reveal that economic teachers demand the students to use the device, some students who are new to using gadgets on particular material in economics subject. The use of gadgets as a medium of learning in the classroom needs to be balanced with the social skills of students. It needs to be a concern that the use of gadgets does not make students an individualistic and